1998
DOI: 10.1093/carcin/19.3.445
|View full text |Cite
|
Sign up to set email alerts
|

Beta2 integrin/ICAM-1 adhesion molecule interactions in cutaneous inflammation and tumor promotion

Abstract: The beta2 integrin (CD 18/CD 11 a, b, c) family of proteins mediate adherence of leukocytes to vascular endothelium and the associated ligand, intercellular adhesion molecule-1 (ICAM-1; CD 54), interacts with beta2 integrin proteins to allow transendothelial migration of leukocytes into sites of inflammation. The present study examines the function of these proteins in a murine model of acute cutaneous inflammation induced following topical application of 12-O-tetradecanoylphorbol-13-acetate (TPA) to the dorsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Since the experiments presented here do not directly address conformational alterations in the external domains of integrin α5β1 associated with FN affinity, it is not possible to formally conclude whether GPER-1-enhanced cellular adhesivity occurs via inside-out signaling. However, our findings are consistent with prior observations that have shown that GPCR activation promotes allosteric changes within the ligand-binding domains of β1, β2, and β3 integrins resulting in enhanced adhesive function [6365]. Our findings suggest that enhanced integrin α5β1 adhesive action of breast cancer cells for FN does not appear to be solely relegated to signaling by GPER-1, as angiotensin II stimulation of breast cancer cells also enhanced fibrillogenesis (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Since the experiments presented here do not directly address conformational alterations in the external domains of integrin α5β1 associated with FN affinity, it is not possible to formally conclude whether GPER-1-enhanced cellular adhesivity occurs via inside-out signaling. However, our findings are consistent with prior observations that have shown that GPCR activation promotes allosteric changes within the ligand-binding domains of β1, β2, and β3 integrins resulting in enhanced adhesive function [6365]. Our findings suggest that enhanced integrin α5β1 adhesive action of breast cancer cells for FN does not appear to be solely relegated to signaling by GPER-1, as angiotensin II stimulation of breast cancer cells also enhanced fibrillogenesis (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…For example, affinity upregulation of integrin αllbβ 3 for its ligand fibrinogen, a key event in thrombus formation, occurs in response to stimulation of platelets with ADP, epinephrine, or thrombin, whose receptors are GPCRs [62]. Likewise, β1 and β2 integrins on leukocytes exhibit increased affinity for their adhesive proteins in response to a broad array of immunomodulatory substances that act through GPCRs, including, but not limited to, f-Leu-Met-Phe, chemokine, and complement cascade products [63]. Similarly, our findings here indicate that estrogen action via GPER-1 activates integrin α5β1 resulting in its recruitment to focal adhesions (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its positive feedback, the PECAM-1 homophilic binding intensifies cell junction and gives rise to a tight barrier of endothelium. In the course of diapedesis inclusive of homo- and hetero- interactions of PECAM-1, its crosstalk with integrin α v β 3 establishes adhesion between leukocyte and endothelia cells as well as association between cell adhesion molecules and integrins including VCAM-1/α 4 and ICAM/β 2 181920. Moreover, PECAM-1 could associate with CD38 on lymphocytes and CD177 on neutrophils and may work in the regulation of diapedesis according to previous studies2122.…”
mentioning
confidence: 74%
“…These genes encode cytokines, chemokines, kinases, and cell-adhesion molecules, including TNF-α (21), IL-8 (22), mitogenactivated protein kinase kinase kinase 8 (MAP3K8) (23), and integrin β2 (ITGB2) (24), whose roles are widely accepted to be essential in inflammation and tumorigenesis. Therefore, p65 is dimethylated on R30 by PRMT5, which profoundly affects its biological activity.…”
Section: Discussionmentioning
confidence: 99%